2021
DOI: 10.1186/s12301-021-00255-6
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic outcomes of grafted tubularized incised plate urethroplasty in primary distal penile hypospadias: prospective comparative study with the classic Snodgrass repair

Abstract: Background To compare the outcomes between classic tubularized incised plate (C-TIP), known as Snodgrass urethroplasty, and grafted TIP (G-TIP) in the repair of primary distal penile hypospadias. Methods Parents of all children presented to our tertiary care institution with primary distal penile hypospadias were asked to participate in this study. Patients were equally randomized using closed envelope method into two groups; Group A underwent repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The difference in HOSE scores between the two groups was statistically significant. Our results in group A were comparable to those of the study conducted by Ahmed et al 28 The limitations of this study include the relatively short follow-up period and small sample size. The small sample size may have resulted in an underpowered subgroup analysis of complications.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The difference in HOSE scores between the two groups was statistically significant. Our results in group A were comparable to those of the study conducted by Ahmed et al 28 The limitations of this study include the relatively short follow-up period and small sample size. The small sample size may have resulted in an underpowered subgroup analysis of complications.…”
Section: Discussionsupporting
confidence: 88%
“…Despite this, it has been validated as an objective pediatric scoring system for assessing cosmetic outcomes of hypospadias repair. 12,27, 28 Ahmed et al 28 used the HOSE score to assess cosmetic outcomes in 110 patients after 6 months of repair, comparing grafted TIPU versus classic TIPU in distal hypospadias. The mean total HOSE score was 15.4 and 15.6 in grafted TIPU and classic TIPU, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the remaining three studies, there were some concern in the domain of randomization 7 16 and concern over missing outcome data. 10 …”
Section: Resultsmentioning
confidence: 99%
“…Mohammed et al 18 reported this outcome as a mean without range or SD. Ahmed et al 10 reported that a few of their patients failed to report for follow-up. For the meta-analysis of the outcome of operative time, we considered the total number of patients operated on by surgeons; however, for the analysis of the remaining outcome measures, we calculated the total number of patients who had completed follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation